An Overview of Renal Diseases in Children in Pokhara - Malla, T; Malla, KK; Thapalial, A; Sharma, MS (Journal of Nepal Paediatric Society, 2009)
<!–[if gte mso 9]> mother 11.6568 <![endif]–><!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Objective: To determine the current pattern and prevalence of renal diseases in childhood in this region of Nepal. Material and Methods: A retrospective study of the renal diseases in children attending the Pediatric OPD and those hospitalised in Manipal Teaching Hospital, Pokhara was done over a period of 6 years (September 2000- September 2006). A detailed clinical and laboratory evaluation was performed at baseline. The children were managed according to disease diagnosed. These cases are under follow up and some have undergone surgical treatment. Results: 228 children (123 boys & 105girls) were diagnosed to have renal disease. Among them 39.5% had urinary tract infection (UTI), 30.7 % were suffering from acute glomerulonephritis (AGN), 17.5% were cases of nephrotic syndrome (NS) and 12 % had some other problems for example, 6.14% had genetic defects, 2.63% had renal Stone, 2.2% had pre-renal acute renal failure, unexplained recurrent hematuria in 1.3%. All the cases of UTI underwent through investigation and were treated accordingly. All cases of AGN are planned for follow up for 1½ yrs and among them 3 required biopsy till date. All cases of NS are under regular follow-ups and 2 have undergone biopsy. Renal stone was operated successfully. All cases of acute and chronic renal failures had required dialysis. Out of 5 (2.5%) chronic renal failures, 2 with end stage renal disease expired after repeated hemodialysis and three are still requiring dialysis. Among the obstructive uropathies, 43 % had renal stone, 36 % had posterior urethral valve and 21% VUR. Conclusion: It can be concluded that renal disease is not uncommon in children. It can be completely cured with proper and adequate treatment. Sometimes it has a bad prognosis when it reaches end stage renal disease. Early recognition, timely treatment and regular follow up are mandatory in management of children with renal diseases. Key words: Renal disease pattern, UTI, AGN, NS, Obstructive Uropathy, Renal failure doi:10.3126/jnps.v27i2.1414 J. Nepal Paediatr. Soc. Vol.27(2) p.75-78